Determinan Nilai Perusahaan Dengan Struktur Modal Sebagai Variabel Intervening pada Perusahaan LQ 45 Di Indonesia - Warsono; Fathoni Zoebaedi (Fakultas Ekonomi Dan Bisnis Universitas Pancasila, 2019)
This study aims to examine determinants (factors that affect) the value of the company that is profitability, liquidity and size of companies using capital structure as an intervening variable. The population in this study is a company that was selected in LQ 45 listed in the Indonesia Stock Exchange from august to january 2012- 2016 with 85 samples selected using purposive sampling. Research hypothesis testing using the Simultaneous Equation Modelling with Warpl PLS 6.0. Results of the analysis showed that profitability, liquidity and size significantly influence the firm value and capital structure. Capital structure is also able to mediate the effect of profitability, liquidity and size to the firm value.